Glycemic Index of Some Commonly Consumed Staples in Nigeria - E.N., Okafor; Onyechi, I.; Ozumba, A.U.; Elemo, G.N.; Kayode, O.F.; Asieba, G.O. (Pakistan Journal of Nutrition, 2011)
Blood glucose response and glycemic index of some common staples consumed in Nigeria were investigated. Eleven healthy volunteers (2 females and 9 males), mean aged 32.63 years and a mean BMI value of 21.38kg/m2 were eventually selected. Subjects were studied on separate occasions in the morning after a 10-12h overnight fast. After fasting blood glucose was taken, subjects ate a test meal at a comfortable pace within 15 mins and further blood glucose response were taken at intervals of 15mins then 30 mins, over a period of 2hrs. The blood glucose response to the staples increased with time, reaching their peak after 45 min. except for sweet potato which peaked after 30 min., after which a fall in the responses with increasing time was observed. Glycemic index values ranged from 56 to 62. Boiled rice was observed to have the lowest value of 56, this was followed by boiled yam and plantain with values of 58 respectively. The highest GI was observed in boiled sweet potato and beans with a value of 62 respectively. These values were observed not to be significantly different. Results from this study indicates medium GI values of staples commonly consumed in Nigeria.